Blood Eosinophils Are Associated with Efficacy of Targeted Therapy in Patients with Advanced Melanoma - Wendlinger, Simone; Wohlfarth, Jonas; Kreft, Sophia; Siedel, Claudia; Kilian, Teresa; Dischinger, Ulrich; Heppt, Markus; Wistuba-Hamprecht, Kilian; Meier, Friedegund; Goebeler, Matthias; Schadendorf, Dirk; Gesierich, Anja; et al. (Cancers, 2022)
Background: Eosinophils appear to contribute to the efficacy of immunotherapy and their frequency was suggested as a predictive biomarker. Whether this observation could be transferred to patients treated with targeted therapy remains unknown. Methods: Blood and serum samples of healthy controls and 216 patients with advanced melanoma were prospectively and retrospectively collected. Freshly isolated eosinophils were phenotypically characterized by flow cytometry and co-cultured in vitro with melanoma cells to assess cytotoxicity. Soluble serum markers and peripheral blood counts were used for correlative studies. Results: Eosinophil-mediated cytotoxicity towards melanoma cells, as well as phenotypic characteristics, were similar when comparing healthy donors and patients. However, high relative pre-treatment eosinophil counts were significantly associated with response to MAPKi (p = 0.013). Eosinophil-mediated cytotoxicity towards melanoma cells is dose-dependent and requires proximity of eosinophils and their target in vitro. Treatment with targeted therapy in the presence of eosinophils results in an additive tumoricidal effect. Additionally, melanoma cells affected eosinophil phenotype upon co-culture. Conclusion: High pre-treatment eosinophil counts in advanced melanoma patients were associated with a significantly improved response to MAPKi. Functionally, eosinophils show potent cytotoxicity towards melanoma cells, which can be reinforced by MAPKi. Further studies are needed to unravel the molecular mechanisms of our observations.
CRIS-Team Scopus Importer:2022-05-20
Keywords: biomarker; eosinophils; melanoma